Aplikasi Undian Rejeki Nasabah Berbasis Nodejs Dengan Metode Shuffle (Information Technology and Telematics, 2015)
Abstract-- While this is very much a product of the company held a lottery to increase the number of consumer markets, for example, a bank with a lot of competitors, set the strategy and invite a lot of customers to join and provide investment for the bank .One of them is to hold a lottery, the lottery The customers vying to boost its balance in order to get the prize. Seeing this situation, will be made an application making it easier for the lottery draw customer data that reach millions of account numbers. In making an application using the node js lottery. Applications lottery windfall customer starts with a user accesses an application that is to start the lottery by pressing Hotkeys start then stop then it moves the data will be the winner, when the lottery has reached sequence to eight the lottery is completed and the list of winners can be seen on the menu report. The draw can be seen by all customers. In making the application lottery windfall customers used method is a method shuffle, to transform a given input sequence randomly. Permutations generated by this algorithm appears with equal probability. Keywords: Applications, sweepstakes, nodejs, random, Bank Cimb Niaga.